2021
DOI: 10.1172/jci.insight.138183
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 2 protects against acute kidney injury by regulating autophagy via Beclin-1 pathway

Abstract: The mitochondrial enzyme acetaldehyde dehydrogenase 2 (ALDH2) catalyzes the detoxification of acetaldehyde and endogenous lipid aldehydes. Approximately 40% of East Asians, accounting for 8% of the human population, carry the E504K mutation in ALDH2 that leads to accumulation of toxic reactive aldehydes and increases the risk for cardiovascular disease (CVD), cancer and Alzheimer's, among other diseases. However, the role of ALDH2 in acute kidney injury (AKI) remains poorly defined and is therefore the subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…Though the exact mechanisms needed further exploration, ALDH2 inhibition can directly promote ferroptosis in animal models 42 43 while increased in ALDH2 KO mice 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the exact mechanisms needed further exploration, ALDH2 inhibition can directly promote ferroptosis in animal models 42 43 while increased in ALDH2 KO mice 44 …”
Section: Discussionmentioning
confidence: 99%
“…42 The concentrations of MDA (production of ferroptosis) and LPO were significantly decreased after ALDH2 activation, 43 while increased in ALDH2 KO mice. 44 Taken together, the disturbed FA metabolism and accumulated FA after acute hypobaric hypoxia exposure may evoke neuronal ferroptosis, and subsequent neurological dysfunction.…”
Section: Nano-packed Coenzyme Q10 Prevented Neuronal Ferroptosis Unde...mentioning
confidence: 99%
“…Recently, one study demonstrated for the first time that Alda-1 treatment alleviated intestinal IR injury through the inhibition of oxidative stress, inflammatory response, and cell apoptosis ( 13 ). Two other studies demonstrated that ALDH2 overexpression mitigated IR-induced acute kidney injury by regulating cell autophagy via the beclin-1 pathway, and its activation by Alda-1 treatment alleviated renal IR injury in hypothermic machine perfusion through the Akt-mTOR autophagy signaling pathway ( 12 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the CPR+Alda-1 group, a dose of 0.88 mg/kg of Alda-1 (Selleck Chemicals LLC., Houston, TX) was intravenously administered at 5 min after successful CPR. This dose of Alda-1 was chosen based on the previous studies and the principle of dose conversion ( 13 , 18 , 19 ), in which Alda-1 treatment was shown to effectively alleviate regional renal and intestinal IR injury in those small-animal models. In the other two groups, the same volume of vehicles was intravenously infused at the same time point.…”
Section: Methodsmentioning
confidence: 99%
“…ALDH2 is involved in the oxidative production of ATP in the mitochondria, it reduces the reactive oxygen species (ROS) formation, attenuates the cellular response to oxidative stress, as evidenced by in vivo and in vitro studies, and it protects against ischemia–reperfusion injury in organs like heart, lung and gut 46 . In particular, ALDH2 protects renal tubular epithelial cells from oxidative stress and maintains the homeostasis of the kidney in the course of renal ischemia–reperfusion injury 47 . It has been hypothesized that the protective mechanisms of ALDH2 induces a reduced production of ROS by promoting autophagy, through the upregulation of the Beclin-1 pathway and the release of Bcl-2 47 .…”
Section: Discussionmentioning
confidence: 99%